Dual vocational education and training systems in Europe : lessons learned from Austria, Germany and Switzerland - Bauer, Waldemar [Verfasser]; Gessler, Michael [Verfasser] (My University, 2017)
"Due to economic crisis and high youth unemployment, skills development is a priority field in many countries. This is related to the considerable interest on the part of policy makers, and the close links between VET, economic strength and the social issues associated with employment. The current debate has caused an increasing international interest in the dual system in Europe and triggered a trend to transfer such VET systems, or parts of it, to foreign countries. In a comparative perspective, three dual models in Europe with a long tradition have been analysed (Austria, Germany and Switzerland). In our overviews, we have added two more countries: Netherlands and Norway. Because of the limited space, these countries are not covered in the in-depth analyse. The following dimensions have been derived: structure and governance of the Dual VET System. The comparison shows that Dual Systems can have different configurations: legislation (integrated/separated), role of the politics (unified/divided), competent bodies on the regional level (state/economy), representatives of the working world (social partners/professional associations), subsidies (yes/no), intermediate organisations (yes/no), vocational education and Higher Education (permeability/barriers) and training costs (benefits/ loss). We can conclude from these observations that two different types of Dual VET Systems can be identified: An (1) unified Dual VET System under state responsibility with shared competence between state and economy (e.g. Switzerland) and a (2) divided Dual VET System under state responsibility but mainly directed by the economy (e.g. Germany)." (authors' abtract; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.1 Westeuropa; I 2.1 Deutschland; Berufsbildungssystem; Duales System; Bildungssteuerung; Internationaler Vergleich; Bundesrepublik Deutschland; Schweiz; Österreich